Grain Macronutrient Concentrations in Diverse Wheat Landraces under Optimum Fertilizer Management in Pakistan (SAARC Journal of Agriculture, 2026)
Macronutrients concentration is an important benchmark to evaluate wheat variety for grain yield and quality parameters. The low nutrients density in grain is bound to affect nutrition quality and causing malnutrition problem and hindrance meeting UN sustainable development goals (UN-SDGs). Grain macronutrients concentration was determined in ninety-seven (97) wheat genotypes. Results showed that all wheat landraces were deficient in major elements. The low nutrients status can be attributed to inadequate supply of these nutrients-based fertilizers in wheat production system and soil characteristics.   SAARC J. Agric., 23(2): 285-293 (2025)